CUSTOM AS LAW IN ENGLISH LAW. (12th July 2017) - Duxbury, Neil
Abstract: This article considers prescription as a customary standard of legal validity which enables judges to identify certain customs as law even though the status of those customs as law cannot be ascribed to a law-making authority. Although claims as to customs having prescribed are often bound up with claims as to the quality (as opposed to the validity) of custom as law, prescribed custom is properly conceived to be a feature of the rule of recognition – a criterion by which a court can identify, and declare, a custom as already existing law as distinct from both custom without the force of law and custom turned into positive law.